An Approach to Mixed PnAsm Ligand Complexes1. Issue 1 (13th November 2013) - Schwarzmaier, Christoph; Bodensteiner, Michael; Timoshkin, Alexey Y.; Scheer, Manfred
Abstract The reaction of a P4 butterfly complex with yellow arsenic yields the largest mixed PnAsm ligand complexes synthesized to date. [{Cp′′′Fe(CO)2}2(μ, η1:1‐P4)] reacts with As4 to yield [{Cp′′′Fe}2(μ, η4:4‐PnAs4‐n)] and [Cp′′′Fe(η5‐PnAs5‐n)]. Mass spectrometry together with NMR spectroscopy and X‐ray crystallography give clear evidence about the arrangement of the E positions within the cyclo‐E5 and E4 moieties of the products. Moreover, the results of DFT calculations agree well with the experimental determined outcomes. By coordinating the E4 complex [{Cp′′′Fe}2(μ, η4:4‐PnAs4‐n)] with CuCl, a rearrangement of the E positions occurs in favor with a preferred phosphorus coordination towards copper atoms in the resulting 1D polymeric chain.